Building RESTful APIs with Go - Walczak, Bartlomiej (Packt Publishing, 2018)
"REST is an architectural style that tackles the challenges of building scalable web services. APIs provide the fabric through which systems interact, and REST has become synonymous with APIs. The depth, breadth, and ease of use of Go, make it a breeze for developers to work with it to build robust Web APIs. This course will teach you to build a RESTful web server. You will learn to add routing and handle requests, thus making your APIs more RESTful. Later, by testing and profiling your code you will ensure it runs correctly and behaves well at scale. Moving on with security, you will learn to log requests and outcomes of API calls and speed up performance using the Echo framework. By the end of this course, you will have the knowledge you need to start building your own enterprise-grade RESTful web services that are production-ready, secure, scalable, and reliable."--Resource description page